Estimating State-Level Matching Efficiencies in the Indian Labor Market - Woong Lee; Soon-Cheul Lee (East Asian Economic Review (EAER), 2020)
We analyze state-level matching efficiencies in the Indian labor market using stochastic frontier analysis. The key contribution of this research is the estimation of matching efficiencies at the state level because these can be used for a state-level measure of labor market conditions. Next, we explore the relationship between the estimated matching efficiencies and population density, labor market flexibility, and the Ease of Doing Business index, respectively. The results show that matching efficiency is heterogeneous across states with considerable variation in accordance with the regional diversity in India. However, we find that there is little relationship between the estimated matching efficiencies and the labor market conditions of interest, suggesting that other regional diversity affects matching efficiencies across states in India.
Keywords: J20; J40; J60; O53; 330; Matching Function; Matching Efficiency; Indian Labor Market; Stochastic Frontier Model; Population Density; Labor Market Flexibility